National Competitiveness and Productivity Council - Tamsin Greene-Barker; Linda Kane (National Competitiveness and Productivity Council (NCPC), 2020)
The National Competitiveness and Productivity Council's new name and revised Terms of Reference reflect the Council's expanded mandate as Ireland's National Productivity Board. The CSO's Productivity in Ireland 2018 report provides further valuable analysis of productivity developments in the Irish economy. More research and analysis is needed to better inform the design of policies to enhance productivity in all sectors of the Irish economy, especially in SMEs, as the economy recovers.
Keywords: 330